Back Cover: A 3D Organically Synthesized Porous Carbon Material for Lithium‐Ion Batteries (Angew. Chem. Int. Ed. 37/2018). Issue 37 (10th August 2018) - Zhao, Ziqiang; Das, Saikat; Xing, Guolong; Fayon, Pierre; Heasman, Patrick; Jay, Michael; Bailey, Steven; Lambert, Colin; Yamada, Hiroki; Wakihara, Toru; Trewin, Abbie; Ben, Teng; et al.
Abstract : Porous carbon could not be designed on a molecular level until now. In their Communication on page 11952 ff., T. Ben, A. Trewin, and co‐workers report an organic synthetic strategy to attain porous carbon by design on the molecular level. This sp–sp 3 hybridized porous carbon, OSPC‐1, is a highly promising anode material for lithium‐ion batteries with high capacity and resistance to dendrite formation. This method has the potential to extend research frontiers to a new family of porous carbon materials.